A study on key success of contractors under Enem Corporation Sdn Bhd / Awatif Saari - Saari, Awatif (Faculty of Business and Management, 2010)
As requirement by subject Industrial Training Report (OPM 662), I have completed this research on “Key Success of Contractors under Enem Corporation Sdn Bhd”. In this research, there are three independent variables that affect key success have been identified which are business skills, management skills and access to capital. Research has been doing on two respondents which are the contractors of Enem Corporation Sdn Bhd. I have taken 108 people to be my respondents and that was the samples of this research. Objectives of the study are to investigate the key success contractors of Enem Corporation Sdn Bhd, the objectives are to determine the main success factors of contractors under Enem Corporation Sdn Bhd and to identify the relationship between independent variables (business skills, management skills and access to capital) and dependent variable (key success factors).